Identification and characterization of Aspergillus niger causing collar rot of groundnut (Arachis hypogaea) - XUAN HIEU NGUYEN; THI MINH NGA NGUYEN; DUC HUY NGUYEN; QUANG CO NGUYEN; THI THUYET CAO; THI THUY HOAI PHAM; THI THU THUY NGUYEN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nguyen XH, Nguyen TMN, Nguyen DH, Nguyen QC, Cao TT, Pham TTH, Nguyen TTT. 2023. Identification and characterization of Aspergillus niger causing collar rot of groundnut (Arachis hypogaea). Biodiversitas 24: 2556-2562. Groundnut (Arachis hypogaea L.) is an economically important legume crop in Vietnam and many other countries worldwide. Groundnut cultivation is affected by many biotic and abiotic stresses. Among biotic stresses, groundnut is attacked by many fungal, bacterial and viral pathogens. The most harmful fungal diseases are rust, stem rot, collar rot and other soil borne diseases. Collar rot caused by Aspergillus niger is one of the most important disease of groundnut extensive in Vietnam and worldwide. In this study, symptomatic infected plant samples were collected from nine different locations in Quang Tri and Thua Thien Hue provinces, Vietnam Isolated fungal species were identified on the basis of morphological characterization, and molecular level. The pathogenicity of fungal species was confirmed on the basis of Koch's postulates. The result showed that a total of nine fungal strains were isolated from infected groundnut samples. Morphological analysis results showed that all isolates exhibited A. niger characteristics, including black colony, biseriate conidia, hyaline conidiophores and sterigmata. Pathogenicity test showed that all nine A. niger isolates caused collar rot disease in groundnuts. Further molecular identification based on ITS1-4 region nucleotides comparison indicated that selected two isolates, namely QT1 and H17 belonged to A. niger. Further research should be done to find antagonistic microorganisms isolates for the bio-control of A. niger.